2022
DOI: 10.1037/bne0000500
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy and function of the postrhinal cortex.

Abstract: The parahippocampal cortex (PHC) in the primate brain is implicated in the medial temporal lobe (MTL) memory network for spatial and episodic memory, but the precise function of this region remains unclear. Importantly, the rodent postrhinal cortex (POR) provides a structural and connectional homolog to the primate PHC. This homology permits the use of the powerful tools available in rodent models to better understand the function of the PHC in the human and nonhuman primate brains. Although many articles have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…Cases MO and MI both had damage that extended to a portion of the posterior parahippocampal cortex, and these animals displayed deficits that were more severe than average. This is consistent with the critical role for the parahippocampal cortex as a route for spatial information to reach the hippocampus (Aggleton, 2012;Estela-Pro & Burwell, 2022), and our prior study on PHC (LaFlamme et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Cases MO and MI both had damage that extended to a portion of the posterior parahippocampal cortex, and these animals displayed deficits that were more severe than average. This is consistent with the critical role for the parahippocampal cortex as a route for spatial information to reach the hippocampus (Aggleton, 2012;Estela-Pro & Burwell, 2022), and our prior study on PHC (LaFlamme et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…More updated reviews of function and anatomy have called for a reappraisal of this distinction pointing to mixing of these streams at multiple levels [19,17,20]. Understanding the role that EC plays in refining, gating, or transforming sensory information is fundamental to understanding how and why place cells form, as well as the mechanisms underlying neuronal navigation and memory systems.…”
Section: Chapter 1: Introduction and Backgroundmentioning
confidence: 99%
“…We have proposed that the POR represents environmental contexts including the spatial layout of objects and patterns, that the POR automatically monitors the current context for changes and updates context representations when changes occur, and that object and pattern information arrives to the POR directly from the PER (Estela-Pro and Burwell, 2022, Furtak et al, 2012, Ho and Burwell, 2014, Peng and Burwell, 2021, Burwell and Hafeman, 2003). Such representations are available to multiple brain regions, for example, the hippocampus for associative learning (Agster and Burwell, 2013) and prefrontal cortex for context guided behavior and cognition (Hwang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested that the PER provides object and pattern information to the hippocampus for associative learning and episodic memory and to the POR for representing the local physical context (Heimer-McGinn et al, 2017). Such information could be used to represent the local physical context (Estela-Pro and Burwell, 2022, Ho and Burwell, 2014, Peng and Burwell, 2021). POR representations of context are available to other brain regions for context-guided behavior and cognition, for example, the prefrontal cortex (Hwang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%